HARALD BODENSCHATZ, VICTORIA GRAU, CHIRTIANE POST, MAX WELCH GUERRA (eds.) - Urban Planning in Nazi Germany. Attack, triumph, terror, in the European context 1933-1945 - Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
HARALD BODENSCHATZ, VICTORIA GRAU, CHIRTIANE POST, MAX WELCH GUERRA (eds.)Urban Planning in Nazi Germany. Attack, triumph, terror, in the European context 1933-1945Dom publishers, Berlín, 2025, 623 pp. 52 €Idioma: inglés, alemánISBN: 978-2-88915-472-2